Beyond micro-credit : putting development back into micro-finance - Fisher, Thomas; Sriram, M. S.; Harper, Malcolm, 1935-; Oxfam; New Economics Foundation (New Delhi : Vistaar Publications ; Oxford : Oxfam, 2002)
The book analyses India micro-finance in depth to explore how development can be put back into micro-finance. It sets out how micro-finance can be designed, in practice, to contribute to wide range of developmental objectives including providing social and economic security among others.
"Published in association with New Economics Foundation, London."
Includes bibliographical references (p. [372]-379) and index.
nmn 11/06/13
Loans
Keywords: Microfinance -- India; Microfinance; Economic development projects -- India; Economic development